Asset market response to monetary policy news from SNB press releases - Hendrik Hüning (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2016)
This paper analyses the effects of Swiss National Bank (SNB) communication on asset prices. It distinguishes between different monetary policy news contained in press releases following a monetary policy decision. Employing a latent variable approach and event-study methods, I find that medium- and long-term bond yields respond to changes in the communicated inflation and GDP forecasts as well as to the degree of pessimism expressed in press releases. Exchange rates mainly react to changes in the GDP forecast while stocks do not react to SNB communication on monetary policy announcement days. Additionally, short-term expectations about the future path of the policy rate are driven by the communicated inflation forecast. The results underline the role of qualitative news next to quantitative forecasts in influencing market expectations and asset prices.
Keywords: E43; E52; G12; 330; monetary policy communication; asset markets